Morpho-genetic characterization of black-husked small-grain aromatic rice landrace Kalojira of West Bengal - Ghosh, Mrityunjay; Pyngrope, DM; Das, Sripriya; Das, B; Roy, Koushik; Banerjee, Sibajee; Gorain, J; Sarkar, Sutanu; Ghose, TK (ORYZA-An International Journal of Rice, 2023)
The morpho-genetic characterization of Kalojira, a black-husked non-Basmati type scented rice landrace, was done at Bidhan Chandra Krishi Viswavidyalaya (BCKV), Kalyani, West Bengal, India during kharif (wet) season of 2013, 2014 for DUS test, followed by 2019 and 2020 for confirmation of recorded traits, and molecular study was conducted at Bose Institute, Kolkata. The long-statured plants (scale 7, 140-150 cm height) had less foliage and stiff culm with late heading (119±4 days) and late maturity (scale 7, 151±4 days). The bi-sexual flower of the genotype consisted of six yellow-coloured plump anthers and an ovary with white-coloured feathery stigma. The short-sized matured grain (4.9 mm) had black coloured lemma-palea without awn, purple sterile lemma and low test weight (13.1 g). The white-coloured short-bold type kernels (length 3.7 mm and width 2.1 mm) had low amylose content (18.0%), medium gelatinization temperature (alkali spreading value 3.1) and medium-strong aroma (score 2.4). The DNA-based study using 23 simple sequence repeat (SSR) markers revealed that four markers (RM 149, RM 339, RM 341 and RM 569) made greater genetic distances (276 vs. 247 bp, 180 vs. 143 bp, 141 vs. 175 bp, and 194 vs. 168 bp, respectively) between Kalojira and IR 36 in the investigation.